The new program of stimulation of economy of China - I. A. Nasibov (Vestnik MGIMO-Universiteta)
Not only have the effects of the global financial and economic crisis provoked the slowdown in economic growth in China. A Chinese government policy was also aimed at cooling the economy to remove the existing socio-economic imbalances. As a result of the crisis and the actions of the government of China's economic growth fell to a critical level. In this situation, the government of China has decided to launch a new program to stimulate the national economy. However, this program is qualitatively different from the incentive program of 2008-2009.